The influence of different curriculum designs on students' dropout rate : a case study (2018)
The relationship between students' withdrawal and educational variables has generated a considerable number of publications. As the explosion of information in sciences and integration theories led to creating different curriculum designs, it has been assumed that differences among designs explain academic success and, therefore, students' retention. However, little attention has been given to examine explicitly how diverse designs influence dropout rates in practice, which questions if decisions to reform curricula are sufficiently informed. This article describes our curriculum reform, which exposes our former and current curriculum designs as having had dissimilar dropout percentages. Furthermore, we aimed to explore the influence of different curriculum designs on students' dropout rates. The conclusion is that dropout variations may be explained not only because of the curriculum design itself, but also because of the power relationship changes between teachers and students that brought out the design change. Consequently, more research is needed to fully understand the political implications of different curriculum designs and their influence on dropout rates.